Thermal buckling of imperfect functionally graded cylindrical shells according to Wan-Donnell model - Tung, Hoang Van; Duc, Nguyen Dinh (Vietnam Journal of Mechanics, 2008)
A thermal buckling analysis of imperfect circular cylindrical shells of functionally graded material is considered. The material properties are assumed varying as a power form of thickness coordinate variable. The Donnell equilibrium and stability equations are considered and the Wan-Donnell model for initial geometrical imperfection is adopted. The thermal loads include the uniform temperature rise and nonlinear temperature change across the thickness of shell. A closed form solution for the thermal buckling of simply supported cylindrical FG shell under the described thermal loads is obtained. The influences of the relative thickness, the imperfection size and the power law index on buckling thermal loads are all discussed.